An Analysis of Figurative Language Used in William Shakespeare’s Sonnet Poem - Alwi Nurzen, Sayid; Mutmainnah Sopandji, Nada (STKIP PGRI Ponorogo Press, 2024)
This research examines the use of figurative language in William Shakespeare's sonnets, focusing on the use of complex literary devices such as simile, metaphor, personification, hyperbole, metonymic imagery, alliteration, repetition, parallelism, and antithesis. By analyzing these elements in Sonnet 18 and Sonnet 116, this study reveals how Shakespeare's word choice and literary techniques deepen the themes and emotional resonance of his poetry. The study uses a combination of deconstructive reading, comparative analysis, and reader response theory to provide a comprehensive understanding of figurative language in these sonnets. The analysis identified a total of 20 figurative languages used in Sonnet 18 and Sonnet 116. The findings highlight the enduring impact of Shakespeare's work on the English literary tradition and its relevance in contemporary literary studies.